Undergraduates’ Perceptions of the Usefulness of Smartphones in Accessing Electronic Resources in Academic Libraries - Adamu, Mohammed; Misau, Ali Yakubu (Communicate: Journal of Library and Information Science, 2023)
This study is designed to determine the respondents’ perceptions of the usefulness of smartphones in accessing e-resources in academic libraries. Three specific objectives and three corresponding research questions guided the study. It was used a cross-sectional survey design for the study and the area of the study was Bauchi State University. The population of the study consisted of 947 undergraduates during the 2021/2022 academic session. Simple random sampling was used to determine the sample size of the study which arrived at three hundred and eighty-three (383 respondents. Structured questionnaires were used and collected data for this study. The data collected were coded and entered into SPSS for analysis. The findings revealed that there are no significant differences in the undergraduates’ perceptions of the usefulness of smartphones in accessing electronic resources between male and female respondents as well as among Levels One, Two, and Three respondents respectively. Thus, the two null hypotheses were accepted at the level of (<0.5). Females had higher means scores when compared with their male counterparts in terms of their perceptions of the usefulness of smartphones in accessing e-resources at the academic library. Based on the respondents’ verbatim comments the majority of the respondents perceived the comfort of the use of smartphones in accessing e-resources for their coursework, assignments, and research in the academic library studied.